2001
DOI: 10.1016/s1074-7613(01)00225-4
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane-Microfilament Linker Ezrin Is Involved in the Formation of the Immunological Synapse and in T Cell Activation

Abstract: Dynamic interactions between membrane and cytoskeleton components are crucial for T cell antigen recognition and subsequent cellular activation. We report here that the membrane-microfilament linker ezrin plays an important role in these processes. First, ezrin relocalizes to the contact area between T cells and stimulatory antigen-presenting cells (APCs), accumulating in F-actin-rich membrane protrusions at the periphery of the immunological synapse. Second, T cell receptor (TCR)-mediated intracellular signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 55 publications
9
160
2
1
Order By: Relevance
“…Loss of Ezrin has been correlated with decreased IL-2 production, [102][103][104] as well as with impaired migration of T-cell signaling microclusters consisting of TCR and downstream signaling components. 105 Moreover, ERM proteins also play a role in cAMP-mediated T-cell repression by regulating PKA signaling.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%
“…Loss of Ezrin has been correlated with decreased IL-2 production, [102][103][104] as well as with impaired migration of T-cell signaling microclusters consisting of TCR and downstream signaling components. 105 Moreover, ERM proteins also play a role in cAMP-mediated T-cell repression by regulating PKA signaling.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%
“…On the basis of previous reports, [38][39][40][41][42] we analyzed the capability of HIV-1 gp120-CD4 binding to trigger ezrin Tyrphosphorylation in T lymphocytes (Figure 1c-d). The total cell extracts of PBLs treated with gp120 and/or recombinant IL2 were immunoprecipitated using an anti-ezrin mAb and blotted with an anti P-tyr mAb, in order to test the presence of the Tyrphosphorylated form of ezrin.…”
Section: Gp120/ril-2 Stimuli Induced Ezrin Phosphorylationmentioning
confidence: 99%
“…41 Moreover, ezrin binding to membrane proteins is involved both in lymphocyte activation and in the formation of the immunological synapse. 42 Connection to actin is of crucial importance in CD95-mediated apoptosis, both in predisposing T lymphocytes to CD95-mediated apoptosis, 43 and in allowing the early steps of CD95 signaling. 44 Particularly, we have shown that the CD95 polarization, due to the ezrin-mediated CD95/actin association, is the key in rendering human CD4 þ T lymphocytes susceptible to CD95-mediated apoptosis.…”
mentioning
confidence: 99%
“…How ERM participates in several membrane-associated events in lymphocytes remains unclear. For example, three different roles have been reported for the involvement of ezrin-moesin in immunological synapse (IS) formation: ERM was found to be essential for the assembly of IS and the recruitment of ZAP70 in one group of studies (Roumier et al, 2001;Ilani et al, 2007); ezrin was reported to be completely dispensable for IS formation in another study (Shaffer et al, 2009); and in yet a third proposal, ezrin was also declared to negatively regulate IS formation (Faure et al, 2004). Similarly, opposite effects of ERM have been documented for T-lymphocyte movement; T-cell migration could be enhanced by either ERM phosphorylation (Li et al, 2007) or ERM dephosphorylation (Brown et al, 2003).…”
Section: Discussionmentioning
confidence: 99%